PENGARUH AUTHENTICITY, INTERACTIVITY, INVOLVEMENT DAN CUSTOMER ENGAGEMENT DALAM MEMPREDIKSI COSTUMER LOYALTY PADA PEMESANAN HOTEL MELALUI TRAVELOKA.COM - Valdio Valdio; Margaretha Pink Berlianto (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
The purpose of this study was to determine the effect of authenticity, interactivity and involvement on customer engagement and customer loyalty in ordering hotels at traveloka.com and to determine customer engagement mediating the effect of authenticity, interactivity and involvement on customer loyalty in ordering hotels on traveloka.com. The population of this study were consumers ordering hotels at traveloka.com by distributing questionnaires to 160 samples. This study used a purposive sampling technique. Data analysis in this study used SEM-PLS. The results of this study show that authenticity, interactivity and involvement have a positive effect on customer engagement in booking hotels at traveloka.com. Interactivity has a positive effect on authenticity in booking hotels at traveloka.com. Interactivity and customer engagement have a positive effect on customer loyalty in booking hotels at traveloka.com. Meanwhile, authenticity and involvement have no effect on customer loyalty in booking hotels at traveloka.com. Customer engagement mediates the effect of authenticity, interactivity and involvement on customer loyalty in booking hotels at traveloka.com.